Standardization and quality assessment for human intestinal organoids - Lee, Hana; Yang, Seunghye; Lee, Kyung Jin; Kim, Si-Na; Jeong, Ji-Seon; Kim, Ki Young; Jung, Cho-Rok; Jeon, Sooyeon; Kwon, Dayeon; Lee, Sungin; Lee, Hanbyeol; Park, Chihye; et al. (Frontiers in Cell and Developmental Biology, 2024)
To enhance the practical application of intestinal organoids, it is imperative to establish standardized guidelines. This proposed standardization outlines a comprehensive framework to ensure consistency and reliability in the development, characterization, and application of intestinal organoids. The recommended guidelines encompass crucial parameters, including culture conditions, critical quality attributes, quality control measures, and functional assessments, aimed at fostering a standardized approach across diverse research initiatives. The implementation of these guidelines is anticipated to significantly contribute to the reproducibility and comparability of results in the burgeoning field of intestinal organoid research.